Group portrait of a baseball team in Santa Clara County - Giroux, Eugene G. (photographer):::Creator::::::::::::; Tucker, John O., d. 1928 (studio):::Contributor::::::::::::
Portrait of a unidentified baseball Team "CL." Many of the young baseball players also have the initials "S.C." printed on their left sleeves. There are three different uniforms represented, possibly reflecting multiple strings or separate teams.